A language management approach to language problems integrating macro and micro dimensions - Kimura, Gorō Kurisutofu, 1974-; Fairbrother, Lisa, 1971- (Studies in world language problems,, 2020)
"In recent years there has been increased interest in examining the treatment of language problems across different levels of society, ranging from individual interactional issues to language policy and planning at the national or supra-national level. Among the various approaches proposed to tackle this issue, Language Management Theory (LMT) provides a framework to address behaviour towards language problems on different levels explicitly and comprehensively. Using LMT as a unifying theoretical concept, this volume examines the links between micro and macro dimensions through the analysis of a variety of language problems. This body of work illustrates that the LMT framework is able to show the connection between these dimensions clearly, especially when combined with a conceptualization of the micro and macro dimensions as a continuum of intertwining elements. This volume will appeal to readers interested in individual management in discourse as well as those interested in language policy and planning"--